Proceedings of the 8th Conference of the European Society for Fuzzy Logic and Technology 2013
DOI: 10.2991/eusflat.2013.75
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various types of basic functions on image reconstruction using F-transform

Abstract: Technique of image reconstruction using Ftransform uses basic functions for computation. Radius and partition of these functions affects quality of the reconstruction. In this article we are focusing on influence of the basic function shape on the quality of reconstruction and providing results of nondecreasing, nonincreasing and oscillating examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Differences and influences on computation are described in [8]. We choose basic functions with radius 2 in the first step of reconstruction and radius 4 in the second step because of fully sufficient usage on the input set of testing images.…”
Section: Influence Of Basic Functionsmentioning
confidence: 99%
“…Differences and influences on computation are described in [8]. We choose basic functions with radius 2 in the first step of reconstruction and radius 4 in the second step because of fully sufficient usage on the input set of testing images.…”
Section: Influence Of Basic Functionsmentioning
confidence: 99%
“…It has been shown that F-transform can be applied in image processing for edge detection [4], image filtering [5], image fusion [6], noise reduction [7], etc.…”
Section: Introductionmentioning
confidence: 99%